2007
DOI: 10.1111/j.1439-0434.2007.01196.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Inorganic Elements on the Reduction of Phytophthora Stem Rot Disease of Soybean, the Growth Rate and Zoospore Release of Phytophthora sojae

Abstract: The effects of several inorganic elements contained in B5 medium on Phytophthora stem rot disease reduction of Glycine max (L.) Merr. cv. Chusei-Hikarikuro, fungal growth of Phytophthora sojae isolate and zoospore release were investigated. Application of B5 solution and macro inorganic nutrients in the B5 medium prior to inoculation significantly inhibited infection, compared with controls. Various concentrations of KNO 3 , (NH 4 ) 2 SO 4 , MgSO 4 , CaCl 2 and NaH 2 PO 4 in the presence of macro inorganic nut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 26 publications
3
25
1
Order By: Relevance
“…Methods for managing economic losses to Phytophthora include fungicides (Anderson and Buzzell 1982), planting cultivars with race-specific or partial resistance (Dorrance et al 2003), soil drainage (Schmitthenner 1985), tillage practices (Workneh et al 1998), and calcium applications (Sugimoto et al 2005(Sugimoto et al , 2007(Sugimoto et al , 2008b(Sugimoto et al , 2009(Sugimoto et al , 2010. Schmitthenner (1999) reported that the most effective method to reduce damage would be to plant resistant cultivars, and genes conditioning resistance to P. sojae (Rps genes) have been widely used in commercial soybean cultivars for controlling Phytophthora stem and root rot disease (Dorrance and Schmitthenner 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Methods for managing economic losses to Phytophthora include fungicides (Anderson and Buzzell 1982), planting cultivars with race-specific or partial resistance (Dorrance et al 2003), soil drainage (Schmitthenner 1985), tillage practices (Workneh et al 1998), and calcium applications (Sugimoto et al 2005(Sugimoto et al , 2007(Sugimoto et al , 2008b(Sugimoto et al , 2009(Sugimoto et al , 2010. Schmitthenner (1999) reported that the most effective method to reduce damage would be to plant resistant cultivars, and genes conditioning resistance to P. sojae (Rps genes) have been widely used in commercial soybean cultivars for controlling Phytophthora stem and root rot disease (Dorrance and Schmitthenner 2000).…”
Section: Introductionmentioning
confidence: 99%
“…These isolates were tested using the virulence test on G. max ÔTanbakuroÕ and PI103091. Virulence evaluations of isolates were performed using the agar medium inoculation method, and conducted in a test bottle (width = 8 cm, height = 20 cm) using mycelia and not zoospores (Sugimoto et al 2006(Sugimoto et al , 2007. PI103091 was strongly resistant, but ÔTanbakuroÕ was susceptible to all 51 isolates.…”
Section: Methodsmentioning
confidence: 99%
“…Although this disease has been controlled with fungicides (Anderson and Buzzell 1982), calcium application (Sugimoto et al. 2005, 2007), partial resistance (Dorrance et al.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In USA, the main pathogens that cause root rot disease in soybean are Fusarium and Pythium (Ellis et al, 2013). The main pathogenic fungi in Japan are Pythium (Sugimoto et al, 2007), while the main pathogenic fungi in Canada are F. oxysporum and F. graminearum (Thomas et al, 2007). In China, the main pathogens that cause soybean root rot are Fusarium (Ding et al, 2011;Guo et al, 2011;, among these, F. solani is the dominant strain in Shandong (Wu et al, 2008;Pan et al, 2010), F. episphaeria, F. tricinctum and F. oxysporum are the main pathogens in Anhui Province, Huaibei area ), Phytophthora, F. oxysporum, F. solani (Cui et al, 2010 are the dominant pathogens in Fujian Province, and Fusarium, Rhizoctonia, Pythium, and Phytophthora are the dominant pathogens in the Xinjiang autonomous region (Qiao et al, 2007).…”
Section: Introductionmentioning
confidence: 99%